Analysis of the perception of digital skills by apprentices of the administrative management programs of the trade and services center - Moreno Rivas, Lina María
Information and communication technologies (ICT) constitute a fundamental tool in activities developed in the teaching-learning process of the different disciplines of knowledge. In the fourth industrial revolution, the use of ICT is essential in this process, so that they are integrated in a meaningful way; for the benefit of the apprentices. ICT plays an important role in business, since it favors the success of companies and the use of technological tools and allows greater control of their operations. The agents involved as SENA apprentices directly experience the effects of the new digital era, through changes in their work practices, through modifications in their decision-making power and their integration into the world of work. The adoption of ICT represents important new challenges, both for companies through the digital business transformation, and for apprentices from their role as digital citizens of the world.. This research aimed to identify gaps in the learning and appropriation of ICT by apprentices of the programs: Technicians and Technologists in Administrative Management, as a means to propose strategies to strengthen their digital skills, in the Center for Commerce and Services of the Risaralda Region. Through this research it was shown that ICT gaps related to digital skills are present, not only among apprentices, but also among instructors, which is why strengthening and training in digital skills is required, between both. .